Leadership Diversity and Development in the Nation's Cancer Centers. (28th July 2022) - Lerman, Caryn; Hughes-Halbert, Chanita; Falcone, Mary; Gosky, David M; Jensen, Roy A; Lee, Kelvin P; Mitchell, Edith; Odunsi, Kunle; Pegher, Jennifer W; Rodriguez, Elisa; Sanchez, Yolanda; Shaw, Reuben; et al.
Abstract: The capacity and diversity of the oncology leadership workforce has not kept pace with the emerging needs of our increasingly complex cancer centers and the spectrum of challenges our institutions face in reducing the cancer burden in diverse catchment areas. Recognizing the importance of a diverse workforce to reduce cancer inequities, the Association of American Cancer Institutes conducted a survey of its 103 cancer centers to examine diversity in leadership roles from research program leaders to cancer center directors. A total of 82 (80%) centers responded, including 64 National Cancer Institute–designated and 18 emerging centers. Among these 82 respondents, non-Hispanic White individuals comprised 79% of center directors, 82% of deputy directors, 72% of associate directors, and 72% of program leaders. Women are underrepresented in all leadership roles (ranging from 16% for center directors to 45% for associate directors). Although the limited gender, ethnic, and racial diversity of center directors and perhaps deputy directors is less surprising, the demographics of current research program leaders and associate directors exposes a substantial lack of diversity in the traditional cancer center senior leadership pipeline. Sole reliance on the cohort of current center leaders and leadership pipeline is unlikely to produce the diversity in cancer center leadership needed to facilitate the ability of those centers to address the needs of the diverse populations they serve. Informed by these data, this commentary describes some best practices to build a pipeline of emerging leaders who are representative of the diverse populations served by these institutions and who are well positioned to succeed.